The Role Of Job Satisfaction Mediation Variables On The Performance - Veramika BR Sembiring; Pandapotan Na Uli Sun Siregar; Mochammad Fahlevi (Universitas Medan Area, 2021)
The hospitality industry is facing a series of formidable challenges today. Some of these are relatively new, such as the rise in digital commerce, the increasing influence of mobile and social media, and the general decline in brand loyalty. In today's globalization challenges such as growing market opportunities, pressure on shareholders for short term results, continued lack of guest trust, and lack of talented employees. This research was conducted with a sample of 347 budget hotel employees from several budget hotel groups in the Jakarta area. The quantitative research method using SEM with the SmartPLS 3.0 tool used in this study aims to predict path analysis between constructs. Job satisfaction is also an important factor in hotel budgets because several factors that affect employee performance have a significant influence if mediated by job satisfaction. Leaders in the hospitality industry can increase employee job satisfaction by providing different motivators for employees at work and therefore managers should also pay more attention to job aspects related to job satisfaction